FUNGSI DAN PERAN HUMAS DI LEMBAGA PENDIDIKAN - Wina Puspita Sari; Asep Soegiarto (Communicology: Jurnal Ilmu Komunikasi, 2019)
AbstractThe demand for quality human resources in order to compete in the ASEAN Economic Community or the ASEAN Free Market is a challenge for educational institutions to continuously improve their quality in preparing human resources with good morals and have competitive advantages. The current development of public relations is quite encouraging. Public relations or public relations is no longer an unfamiliar term. The term is indeed quite popular and has become popular in Indonesia and the public relations profession is now becoming a "trend" in society. This is indicated by the increasing number of institutions or companies that place public relations in their organizational structures, including in educational institutions. The purpose of this research is to find out the Function and Role of Public Relations in Educational Institutions. The theory used in this study is the role of public relations according to Dozier & Broom as follows: Expert Prescriber, Communication Facilitator, Problem solving process facilitator, Communication technician. The approach and research method used in this study are qualitative descriptive. In this study, it was determined who became the key informants and informants. If it is related to the main problem of the research, the author determines the purposive technique namely: Principal and Deputy Principal. Based on the explanation of the discussion it can be concluded that the position of public relations in the 3 schools that were used as samples differed. There are others that are doubled by other parts but some have started to have a stand-alone public relations department so that the roles and functions of public relations are different. However, the role and function of public relations is still not in accordance with what it should be. There are still schools that feel it is not important to have public relations. Whereas in other schools, the role of public relations has been little seen even though it is only aimed at just one public such as industry. Keyword: PR Function, Role of PR, Public Relations Education Institution